Bioactive phenolic compounds from Australian seaweeds and their impact on gut health - Vigasini Subbiah; Faezeh Ebrahimi; Osman Tuncay Agar; Alistair R. Legione; Frank R. Dunshea; Colin J. Barrow; Hafiz A. R. Suleria (Scientific Reports)
Abstract Seaweed phenolics are increasingly recognized for their health-promoting potential, but their bioavailability and interaction with gut microbiota remain insufficiently understood. This study examined the effects of seaweed phenolics on gut microbiota, short-chain fatty acid production and characterized phenolics during colonic fermentation over 48 h. Results showed that Durvillaea potatorum exhibited the highest total phenolic content (3.14 mg GAE/g) after 8 h of fermentation, while Phyllospora comosa showed peak flavonoid content at 0 h (0.73 mg QE/g). Phlorotannin content was notably elevated in D. potatorum at 12 and 48 h. Antioxidant capacity peaked in Cystophora siliquosa at 48 h (FRAP: 0.14 mg TE/g; TAC: 0.62 mg TE/g), whereas radical scavenging activity was highest in Sargassum fallax and P. comosa at 18 and 24 h, respectively (DPPH: 1.15 mg TE/g; ABTS: 0.36 mg TE/g). In this study, seaweed supplementation modulated the microbiota, resulting in alteration in microbial community structure and diversity. Additionally, short chain fatty acids (SCFAs), including acetic acid, butyric acid, isovaleric acid and total fatty acids were significantly elevated in P. comosa at 12 h. These findings suggest that seaweed-derived phenolics may modulate microbial composition and enhancing SCFAs production.